A robust algorithm to calculate parent β grain shapes and orientations from α phase electron backscatter diffraction data in α/β-titanium alloys. (15th January 2021) - Zaitzeff, Alexander; Pilchak, Adam; Berman, Tracy; Allison, John; Esedoglu, Selim
Graphical abstract: Abstract: This paper presents a new model and open-source algorithm for reconstructing prior β phase orientation and grain shapes from measured α -phase electron backscatter diffraction data in α / β titanium alloys. It is based on the image segmentation model of Mumford and Shah, which includes a regularization term that helps create smooth boundaries and overcomes shortcomings of prior reconstruction techniques. Additionally, the new algorithm is resilient to noise. Our algorithm's effectiveness is demonstrated on simulated and real world data.